Offending Patterns in Cases of Sexual Violence Committed by Multiple Perpetrators - Paquette, Sarah (Victims & offenders, 2024)
Sexual violence committed by multiple perpetrators is a particularly worrying phenomenon given that the severity of psychopathological sequelae for the victims are increased when the sexual offense is committed by more than one offender. Preliminary studies showed that sexual violence committed by solo offenders is different from that of duos or groups of offenders. This study explores the heterogeneity within 983 cases of sexual violence committed by multiple perpetrators, with a focus not only on offenders’ modus operandi, but also victims’ routine activities and situational aspects of the crime. Results from a latent class analysis identified four offending patterns: sexual violence committed by multiple perpetrators where: 1) stranger victims were randomly selected; 2) offenders were geographically mobile; 3) victims were assaulted during social events; and 4) offenders were non-sexually motivated. Findings help identify situational characteristics interacting with offenders’ behaviors and victims’ routine activities associated with sexual violence committed by multiple perpetrators. The implications regarding the heterogeneity of criminal patterns in these forms of violence is discussed in relation to police practice, situational crime prevention strategies, and future research.